2005
DOI: 10.1002/jlcr.950
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient tritium labelling of the nonsteroidal anti‐inflammatory drugs naproxen, tolmetin, and zomepirac

Abstract: SummaryFast and efficient tritium labelling of the nonsteroidal anti-inflammatory drugs naproxen, tolmetin and zomepirac is reported. Naproxen along with its (R)-enantiomer were labelled by catalytic tritium-halogen exchange of the corresponding 5-bromo derivatives providing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Tolmetin 1a has previously been labelled with carbon-14 in the ketone carbon 9 and with tritium in multiple positions on the toluene and pyrazole rings. 10,11 Celecoxib has been labelled with carbon-14 in the toluene 12 and pyrazole rings 13 and with deuterium in the toluene 14 and phenylsulfonamide rings. 15 2 | RESULTS AND DISCUSSION…”
Section: Introductionmentioning
confidence: 99%
“…Tolmetin 1a has previously been labelled with carbon-14 in the ketone carbon 9 and with tritium in multiple positions on the toluene and pyrazole rings. 10,11 Celecoxib has been labelled with carbon-14 in the toluene 12 and pyrazole rings 13 and with deuterium in the toluene 14 and phenylsulfonamide rings. 15 2 | RESULTS AND DISCUSSION…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] It is able to promote deuterium or tritium incorporation into arenes at positions ortho to a directing group such as the carbonyl group. [2][3][4][6][7][8][9] Here we report improvements that can be obtained by adding Crabtree's catalyst to rhodium black.…”
Section: Introductionmentioning
confidence: 99%
“…The field of dehalogenative deuteration has drawn significant attention due to its tremendous potential in the preparation of different drug molecules with a longer lifespan in plasma, which prevents off-target site interactions and/or leads to accomplishing higher efficacy. As a result, incorporation of deuterium in a molecule appeared as clinically highly significant. Deuterium-labeled analogues of the drug are utilized in absorption, distribution, metabolism, and excretion studies and have the potential to facilitate the discovery of new pharmacophores. However, dehalogenative deuteration reactions ,, mainly involved precious transition metal catalysts/ligands and costly deuterium sources or noncatalytic methodologies using sodium amalgam and lithium-halogen exchange, which suffer from harsh conditions and require highly sensitive alkyl-lithium reagents. In 2011, Mutsumi et al demonstrated the deuterated version of this hydrodehalogenation reaction, namely, catalytic dehalogenative deuteration of aromatic nuclei utilizing 2,2′-azobis­(2,4-dimethylvaleronitrile) (V-65) in combination with an organotin reagent and THF- d 8 as deuterium sources, but the necessity of toxic Bu 3 SnH, high temperature, and expensive deuterium sources ( ≈ $630 for 10 g of THF- d 8 , Sigma-Aldrich Cat.…”
Section: Introductionmentioning
confidence: 99%